2022
DOI: 10.1002/ldr.4242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restoration strategies on wetland: A case‐study of Xinqiang River National Wetland Park

Abstract: Accurately understanding the characteristics of a wetland ecological restoration plant communities and their species diversity relationships is the key to improving wetland management and biodiversity protection. To see the effects of restoration strategies implemented in Xinqiang River National Wetland Park, China, we studied 4 models for ecological restoration, namely protection and conservation (PC), reasonable utilization (RU), restoration and reconstruction (RR) and the building of constructed wetland (CW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Further, Song et al [39] indicated that reducing water pollution, protecting biodiversity, maintaining the structural integrity of wetlands, practicing erosion regulation, decreasing flood hazards, and managing stormwater are important measures for protecting wetland parks. As a composite product of 'wetland' and 'park', the coordination problem of wetland park ecological protection and utilization has long attracted academic attention and discussion [21,40,41]. However, few scholars have systematically studied wetland parks from an international perspective based on the viewpoint of multidisciplinary integration.…”
Section: Wetland Park Research Is Increasing In International Academiamentioning
confidence: 99%
“…Further, Song et al [39] indicated that reducing water pollution, protecting biodiversity, maintaining the structural integrity of wetlands, practicing erosion regulation, decreasing flood hazards, and managing stormwater are important measures for protecting wetland parks. As a composite product of 'wetland' and 'park', the coordination problem of wetland park ecological protection and utilization has long attracted academic attention and discussion [21,40,41]. However, few scholars have systematically studied wetland parks from an international perspective based on the viewpoint of multidisciplinary integration.…”
Section: Wetland Park Research Is Increasing In International Academiamentioning
confidence: 99%
“…CWs not only perform effectively in terms of wastewater treatment but also add a substantial amount of organic matter to the soil after the decomposition of plant debris. Additionally, the plants' biomass can be used to produce energy [97,98]. CWs play a positive role in sustaining biomass, managing water storage, and refilling groundwater [99,100].…”
Section: Why Constructed Wetlands Are Being Chosenmentioning
confidence: 99%
“…Many scholars have carried out research on wetland restoration [8], the evaluation of wetland ecological functions [9], and the comprehensive management of wetlands [10] in the YRD. In recent years, the monitoring and prediction of wetland changes [11][12][13][14], the driving mechanisms of wetland changes [15][16][17][18], and wetland protection and restoration [19] in the YRD has received increasing attention. The estimation of wetland biomass [20,21] and carbon storage [22][23][24] has gradually become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%